Analisis Faktor E-Learning Readiness dengan Menggunakan Principal Component Analysis - Nuzhah Al Waaidhoh; Eko Sediyono; Kristoko Dwi Hartomo (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
Technological innovation in the industrial revolution era of 4.0 has changed the concept of learning. For example, the e-learning enables students to learn any where and any time without the limitations of distance, space and time. E-learning brings transformation in the world of education by enabling students to access information, data and learning material in more effective and efficient ways. With some of the benefit soffered by e-learning, many organizations want to apply e-learning system. Implementation of e-learning started with assessing thee-learning readiness. There are many factors found by researchers in the process of assessing e-learning readiness. This study aims to reduce the number of e-learning readiness variabels and to identify the factors that most affect the level of e-learning readiness by using the PCA (Principal Component Analysis) method, so it can help organizations that will implement e-learning to prepare important things in the process of implementation e-learning system. The results obtained show that the three factors that most affect there a diness of implementation e-learning are organization, technology and human resources.